Analysis of phase preparatory demolition of a building - Sobotka, Anna; Sagan, Joanna (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
Demolition can be a stand-alone construction project or its initial phase. As ach project consists of several stages, including the planning and preparation of demolition. In the paper the analysis of activities in the preparatory phase of the demolition, based on the requirements of legal acts, including the Construction Law.